IMPLEMENTASI MODEL PICTURE AND PICTURE BERBANTUAN MEDIA WORDWALL DALAM PEMBELAJARAN MENULIS TEKS EKSPOSISI SISWA FASE E SMK - Tiur Tambunan; Irma Suryani; Lusia Oktri Wini (STKIP Subang, 2026)
This study aims to describe the implementation of the Picture and Picture learning model assisted by Wordwall media in learning to write exposition texts for Phase E students of SMK Negeri 9 Muaro Jambi. The study used a descriptive qualitative approach. The subjects were 30 students of class X TKR Phase E, while the Indonesian language teacher served as a supporting data source. Data collection techniques included observation, interviews, and documentation. The research instruments consisted of teacher and student observation sheets, teaching module observation sheets, teacher and student interview guidelines, exposition text assessment indicators and their detailed indicators covering aspects of content/topic suitability, structure, integration and clarity of flow, linguistic rules, and spelling and grammar. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results showed that learning to write exposition texts with the Picture and Picture model assisted by Wordwall was carried out in two meetings and ran interactively. Visual media in the form of images helped students understand the process flow concretely, while Wordwall increased engagement and learning motivation. Based on the assessment results, the average writing ability score was 86 (very good category), with 18 students in the very good category, 9 students in the good category, and 3 students in the fair category. This finding is in line with several previous studies that demonstrated the effectiveness of the Picture and Picture and Wordwall models in writing learning. Overall, the Picture and Picture model assisted by Wordwall has proven effective in increasing student engagement and the quality of expository text writing.